The Role of Indonesia’s Defense Diplomacy in Realizing the Optimal Code of Conduct in Order to Reduce the Widespread Conflict in the South China Sea Region - Widiyanto, Widiyanto; Anwar, Syaiful; Risdhianto, Agung (PT FORMOSA CENDEKIA GLOBAL, 2024)
In dealing with conflict in a region consisting of several countries, defense diplomacy is an important aspect in strengthening the region in facing threats from other countries, especially if the threat comes from a superpower, as happened in the South China Sea after China used claims. nine dash line which gives rise to the potential for conflict between countries, so for Indonesia, the role of Indonesian defense diplomacy is needed in realizing an optimal code of conduct in order to reduce the spread of conflict in the South China Sea, so referring to this background, this research aims to analyze how cooperation is implemented bilateral or multilateral defense with external forces to increase stability and balance of power in the region and the implementation of Indonesia's current defense diplomacy strategy to respond to conflicts in the South China Sea region. This research uses a qualitative approach with descriptive analysis methods supported by interviews, literature studies, and observation as a method for tracking data and facts, where based on research results it is known that the proposal of several concepts to support the diplomacy strategy played by Indonesia is enough to have a significant domino effect on the Indo-Pacific region by focusing on the value of ASEAN centrality. Indonesia implements their national defense policy strategy by means of diplomacy and international cooperation which continues to be developed, implementing bilateral or multilateral defense cooperation with external powers to increase stability and balance of power in the region, one of which is implemented through the ASEAN Outlook on the Indo-Pacific (AOIP ), After going through several diplomatic processes and also negotiations on organizational dynamics.